Binge eating and binge drinking behaviors: Individual differences in adolescents' identity styles. (March 2014) - Laghi, Fiorenzo; Baiocco, Roberto; Liga, Francesca; Lonigro, Antonia; Baumgartner, Emma
Considering the significant negative consequences that are directly related to binge eating and drinking behaviors, many studies have explored the reasons why adolescents engage in them. This study examined the differences in the development, maintenance, and co-occurrence of "binge" behaviors associated with adolescent's identity style and the level of commitment. One thousand four hundred Italian adolescents completed self-report measures assessing binge behaviors and identity styles. Overall, results show that diffused adolescents were more likely to be engaged in binge eating and binge drinking behaviors than others, validating the idea that the achievement of a consolidated ego identity is important for enhancing well-being.